An observation of prescription behaviors and adherence to guidelines in patients with COPD: real world data from October 2012 to September 2014. (1st September 2016) - Visentin, Elena; Nieri, Dario; Vagaggini, Barbara; Peruzzi, Elena; Paggiaro, Pierluigi
Abstract: Introduction: GOLD guideline recommendations are currently the "gold standard" for the treatment of COPD patients. Objectives: The objective of this analysis was to evaluate compliance with GOLD guidelines in managing COPD patients' treatment by general practitioners (GPs) and pulmonologists. Since inhaled corticosteroid (ICS) use is defined as inappropriate in mild and moderate COPD patients, special attention was paid to ICS therapy use in these classes. Methods: The study was based on the Italian GP database IMS Health Longitudinal Patient Database (IMS Health LPD) and on the Patient Analyzer specialist IMS Health database. The observed cohort included all patients with a diagnosis of COPD, aged 40 years or more, with at least one ATC R03 class prescription, visited by GPs and pulmonologists during four timeframes: October 2012 – March 2013 (cohort 1), April 2013 – September 2013 (cohort 2), October 2013 – March 2014 (cohort 3); April 2014 – September 2014 (cohort 4). Patients were classified into disease severity groups following 2008 GOLD guidelines, based on FEV1 value. Results: Cohorts were quite similar in size (about two thousand patients per cohort). Pulmonologists visited more severe patients than GPs. About 50% of GPs' mild and moderate patients received treatments containing inhaled corticosteroids. Pulmonologists were more adherent to guidelines, with smaller percentages of mild patients treated with therapies containing ICS (ranging from 19.0% to 30.1%). An improvement in adherence was observed during the four time periods, with a decrease in the use of therapies containing ICS in mild and moderate patients. In absolute terms, it emerged that GPs more often prescribe ICS improperly to patients in the mild and moderate severity classes than pulmonologists. Conclusion: Real world data indicate that adherence to GOLD guidelines is only partially met by GPs in their general practice and shows higher prescription appropriateness by pulmonologists.